Digital Storytelling Sebagai Media Pembelajaran Apresiasi Sastra Arab - Perdana, Dyah Adila (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to analyze the effectiveness of using digital storytelling as a learning medium to enhance the Arabic literary appreciation skills of students in the Arabic Language Education program. Digital storytelling is implemented to integrate textual, audio, and visual elements, enabling students not only to understand literary works conceptually but also to reconstruct textual meaning through creative processes. The study employed a descriptive qualitative approach involving classroom observations, analysis of students' digital storytelling projects, and interviews to explore their perceptions. The findings indicate that digital storytelling enhances students’ understanding of intrinsic literary elements, strengthens their interpretative abilities, and fosters aesthetic sensitivity toward Arabic literary texts. This medium also proves effective in creating a more interactive, collaborative, and constructivist learning environment. However, several challenges were identified, including limited digital literacy, variations in Arabic language proficiency, and technical obstacles related to devices and internet connectivity. The study recommends increased technical training, the development of more systematic literary analysis guidelines, and improved supporting facilities to optimize the implementation of digital storytelling in Arabic literary appreciation courses. These findings affirm that digital storytelling is a relevant and promising learning medium for sustainable integration into literary education in the digital era.